Evaluating a gender diversity workshop to promote positive learning environments. Issue 2 (3rd April 2017) - Burford, James; Lucassen, Mathijs F. G.; Hamilton, Thomas
ABSTRACT: Drawing on data from an Aotearoa/New Zealand study of more than 230 secondary students, this article evaluates the potential of a 60-min gender diversity workshop to address bullying and promote positive environments for learning. Students completed pre- and postworkshop questionnaires. The authors used descriptive statistics to summarize results and conducted t -tests to assess the statistical significance of changes from before the workshop to immediately after the workshop. The authors used thematic analysis to analyze open-ended questionnaire responses. In summary, 237 students ( M age = 13.7 years) attending 10 workshops participated in the study. More than 80% of students thought the gender diversity workshop would reduce bullying in schools, and 94% of participants reported that they would recommend the workshop to other young people. There was a significant increase in valuing ( p < .001) and understanding ( p < .001) gender-diverse people before and after the workshop. School cultures were largely perceived to be hard for gender-diverse students; however, many respondents reported a desire to be supportive of their gender-diverse peers. Reducing bullying related to gender identity and expression is very likely to have a positive effect on the mental health and educational achievement of young people. Brief diversity workshops, as a part of a wider suite of educational reforms, have the potential to create safer environments for learning.